Replies to commentaries on the generalizability crisis. (10th February 2022) - Yarkoni, Tal
Abstract: The 38 commentaries on the target article span a broad range of disciplines and perspectives. I have organized my response to the commentaries around three broad questions: First, how serious are the problems discussed in the target article? Second, are there are other, potentially more productive, ways to think about the issues that the target article framed in terms of generalizability? And third, what, if anything, should we collectively do about these problems?